Men as Caregivers : Theory, Research, and Service Implications - Kramer, Betty J.; Thompson, Edward H., Jr., 1945- (Springer series, focus on men (Unnumbered), 2002)
Today, more and more caregivers are male. Despite this fact, the vast majority of research on caregiving has centered on the experience of the female caregiver. This volume addresses the fundamental gap in our knowledge and theories about the growing male subpopulation of caregivers. The authors identify the serious limitations that result from viewing men caregivers through the lens of women's experiences and call.